(untitled) (Aporia, 2020)
In this essay I will address the broad topic of personal identity. This topic deals with the problem of how we can truly claim that a person is the same person throughout his life or indeed over any period of his life. What is it about a person that means I can refer to him as a continuing entity? I will argue that some traditional approaches to identity miss the real question and propose that identity resides in a self’s characteristic interaction with the world.